Comparative Effects of Hatha Yoga and Prenatal Exercise on Physiological and Psychological Outcomes in Primigravid Women: A Randomized Controlled Trial - Fernandez, Veronica; Lesmana, Ronny; Krisnadi, Sofie R.; Susiarno, Hadi; Iskandar, Shelly; Tarawan, Vita Muniarti (Journal of Applied Nursing and Health, 2025)
Background: Primigravid women are prone to stress due to physical and psychological changes during pregnancy, which can lead to hypertension, preeclampsia, preterm birth, fetal growth restriction, and postpartum depression. While non-pharmacological interventions like hatha yoga and prenatal exercise are used to reduce stress, comparative evidence—especially on oxygen saturation (SpO₂)—is limited. This study analyzes the effects of hatha yoga and prenatal exercise on stress, blood pressure, and SpO₂ among primigravid women, and compares both interventions across these outcomes. Methods: This randomized controlled trial (RCT) followed the CONSORT 2010 guidelines. Forty-eight eligible primigravid women were selected using a probability sampling technique, specifically the simple random sampling method. Random numbers were generated using Microsoft Excel to determine participant selection from the maternal cohort register. Inclusion criteria were a normal singleton pregnancy at 24–28 weeks of gestation, maternal age 20–35 years, and normal Body Mass Index (BMI) (18.5–24.9 kg/m²). Exclusion criteria included regular exercise more than twice a week, abnormal fetal heart rate, and scheduled elective cesarean delivery. Participants were randomly assigned to either a hatha yoga group or a prenatal exercise group (24 each). Both interventions were conducted twice weekly for four weeks. Data were analyzed using the Wilcoxon and Mann–Whitney tests. Results: Data were analyzed using the Wilcoxon and Mann-Whitney tests. Median stress scores decreased from 22 to 12 in the hatha yoga group and from 22 to 17 in the prenatal exercise group (p < 0.001). Median SpO₂ increased from 96.88% to 98.38% and from 96.81% to 97.00%, respectively (p = 0.002). Median systolic pressure changed from 120.06 to 121.31 mmHg and 118.75 to 117.44 mmHg (p = 0.009), while diastolic pressure showed no significant difference (p = 0.076). Overall, hatha yoga showed greater improvements in stress, SpO₂, and blood pressure stability than prenatal exercise. Conclusion: Hatha yoga proved more effective than prenatal exercise in reducing stress, increasing SpO2, and stabilizing systolic blood pressure among primigravid women, although no significant difference was found in diastolic pressure. These findings strengthen the evidence supporting yoga as a safe, non-pharmacological approach to enhance maternal physiological and psychological well-being during pregnancy.